Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/aec.12644
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of an invasive grass, but not of native grasses, on plant species richness along a cover gradient

Abstract: Impacts of invasive plants on plant communities are not universal, and effects may differ depending on the life form of the invading species. At three sites in the Brazilian Pampa region, we assessed the effects of invasion by Eragrostis plana Nees, considered to be the most problematic invasive plant in South Brazilian grasslands, on local plant communities. Specifically, we evaluated effects on species richness, community evenness and richness of principal functional groups along an invasion gradient. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
16
0
4
Order By: Relevance
“…Eragrostis plana was an indicator species for grassland subtypes 5, 8 and 9. This species was introduced from Africa and is considered the most problematic invader in the region (Dresseno, Guido, Balogianni, & Overbeck, ; Guido, Vélez‐Martin, Overbeck, & Pillar, ). Another highly invasive species, Cynodon dactylon (L.) Pers.…”
Section: Discussionmentioning
confidence: 99%
“…Eragrostis plana was an indicator species for grassland subtypes 5, 8 and 9. This species was introduced from Africa and is considered the most problematic invader in the region (Dresseno, Guido, Balogianni, & Overbeck, ; Guido, Vélez‐Martin, Overbeck, & Pillar, ). Another highly invasive species, Cynodon dactylon (L.) Pers.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐native grass invasion can represent a huge threat to tropical grasslands, due to the negative impact caused by exotic grasses on native grasses and forbs (e.g. Pivello, Shida & Meirelles, ; Damasceno et al ., in press; Dresseno et al ., in press). In addition to suppressing native species, invasive grasses can lead to a high biomass accumulation, with consequences for fire regimes, including increased fire intensity (Mistry & Berardi, ; Setterfield et al ., ; Gorgone‐Barbosa et al ., ).…”
Section: Resiliencementioning
confidence: 99%
“…Continuous and excessive grazing might be unfavorable and lead to the local exclusion of species (Landsberg, Lavorel, & Stol, ; Milchunas et al., ; Olff & Ritchie, ), as habitat conditions are changed and open soil patches often increase (Nabinger, Dall'Agnol, & Carvalho, ). This can favor the establishment of opportunistic and/or invasive species (Baggio et al., ; Guido, Hoss, & Pillar, ) that then can further reduce local species richness (Dresseno, Guido, Balogianni, & Overbeck, ). Here, we demonstrated that the total amount of plant biomass significantly increased in areas under rotational grazing (Figure ).…”
Section: Discussionmentioning
confidence: 99%